ANALGESIC EFFECTS of SCILLIROSIDE, PROSCILLARIDIN- A and TAXIFOLIN FROM SQUILL BULB (Urginea maritima) on PAINS - Bayazit, Vahdettin; Konar, Vahit (Inst Materials Physics, 2010)
The aim of the present study was to assess the clinical efficacy of proscillaridin-A (C(30)H(42)O(8)), taxifolin (C(15)H(12)O(7)) and scilliroside (C(32)H(44)O(12)) and safety of squill bulb (Urginea maritima) (L.) Baker extract on various pains of spontaneous volunteer patients. In this study, 250 patients were monitored in coats. The average age of these patients were between 40 and 74 years old. Of these 100 were male and 150 female patients. Also, 60 % of proscillaridin-A (C(30)H(42)O(8)), taxifolin (C(15)H(12)O(7)) and scilliroside (C(32)H(44)O(12)) solution in pure glycerin was applied as external on the pain area. ASO, CRP and RF higher values of patiens were significantly decreased (p < 0.05 and p < 0.01). Knee, joint, calf, hip, shoulder, upper back, low back (lumbago), tailbone and fibromyalgia paints of patients were significantly reduced (p < 0.05 and p < 0.01). Squill bulb constituents can reduce the musculoskeletal pains.
Keywords: Squill bulb (Urginea maritima) (L.) Baker; scilliroside; taxifolin; proscillaridin-A; lumbago; fibromyalgia; pain